A NEW MODEL OF PETROLEUM MIGRATION INSPIRED BY EARTHQUAKE AND ITS GENERATING BOUNDARY CONDITIONS - Chen R.; Zhao W.; Wang H.; Qiu Z. (My University, 2007)
Natural and artificial earthquakes can trigger off some acceleratory motion tendency of ground fluids. The motion tendency will behave as some impetus of fluids migration if rock media is the reference frame of fluids migration. Based on the ideal model of pore structure and stress analysis of oil column unconsidering mass diffusion, the occurrence boundary conditions of petroleum migration under the action of earthquake are discussed. Those boundary conditions include the length of oil column, pore size, pore-throat, and different fluid pressure status. The results indicate that earthquake can inspire oil column migration through some special pore structure before fractures appear. The detailed analysis shows that lower pore/throat ratio, bigger radius of pore and longer continuous oil column are good for petroleum migration, that petroleum migration inspired by earthquake becomes easier in turn in the following cases: the lateral vibration of earthquake acts on formations with normal fluid pressure, the vertical vibration with normal fluid pressure, the lateral vibration with abnormal fluid pressure, and the vertical vibration with abnormal fluid pressure.
Keywords: BOUNDARY CONDITIONS; EARTHQUAKE; PETROLEUM MIGRATION; PORE; PRESSURE GRADIENT; SURPLUS PRESSURE; THROAT